Analisis Jenis Kesalahan Siswa Berdasarkan Kriteria Watson Pada Materi Bangun Ruang Sisi Datar - Nursalam Nursalam; Suradi Tahmir; Muhammad Ammar Naufal (Pusat Studi Bahasa dan Publikasi Ilmiah, 2026)
This is a qualitative descriptive study that aims to describe student errors based on Watson's criteria in flat-sided solid geometry material in grade VIII of SMPN 11 Buton. The subjects of this study were grade VIII students. The technique for determining the research subjects was by administering a diagnostic test to select two high-ability subjects and two moderate-ability subjects. Data collection techniques included administering a diagnostic test, administering a math ability test, interviews, and documentation. The results showed that students with high ability made two errors out of eight Watson criteria: incorrect data errors, incorrect procedures, missing data, missing conclusions, conflicting response levels, indirect manipulation, skill hierarchy problems. In addition to the seven categories above, high-ability students made errors in inappropriate procedures and missing conclusions. This means that high-ability students made errors in determining their final grades and did not write conclusions from their answers. Then, for subjects with low ability, they made 7 types of errors based on Watson's criteria, namely inaccurate data errors, incorrect procedures, missing data, missing conclusions, conflicting response levels, indirect manipulation, and skill hierarchy problems. Subjects with low ability did not make errors in types of errors other than the 7 categories above. This was because the subjects were unable to understand the concept of the problem, were less careful in working on the problem, which impacted the procedure and the results obtained were less accurate.